Kontribusi Need Assessment School Based Budgeting and Outcome Based Education terhadap kinerja guru Sekolah Dasar Dabin I and II di Kecamatan Godong Kabupaten Grobogan - Sari, Frisca Yulian; , Prof. Dr. Sutama, M.Pd; , Dr. Sumardi, M.Si (2016)
The general objective of this research was to examine the contribution of Need Assessment, School-Based Budgeting and Outcome Based Education on the performance of elementary school teachers Dabin I and II in the District Grobogan Godong simultaneously. While the specific objectives of this study are (1) To examine the contribution of Need Assessment of the performance of elementary school teachers Dabin I dan II in the district Godong, (2) To examine the contribution of School-Based Budgeting to the performance of elementary school teachers Dabin I dan II in the district Godong, and (3) To examine the contribution of Outcome Based Education on the performance of elementary school teachers Dabin I dan II in the district Godong. This research is quantitative. The population in this study were 133 elementary school teachers who then retrieved a sample of 100 teachers through a proportional random sampling. The technique of collecting data using questionnaires. Data were analyzed using multiple linear regression analysis, test F-test, t-test, analysis of the coefficient of determination (R2), donations predictors and classical assumption. Results of the study: 1) the need assessment, school-based budgeting, and outcome based education simultaneously contributes to the performance of primary school teachers in the district Godong with α 5% significance level was 112,915 2) Need assessment showed a significant influence on the performance of teachers with sig 0.000 <0.05 and the effective contribution of 32.23%. 3) School-based budgeting showed no significant effect on the performance of teachers with sig 0.000 <0.05 and the effective contribution of 20.1%. 4) Outcome based education showed a significant influence on the performance of teachers with sig 0.000 <0.05 and the effective contribution of 23.66%. 5) The independent variable a contribution of 77.9% of the performance of teachers and 22.1% are influenced by other factors not discussed in this study. Keywords: need assessment, school-based budgeting, outcome based-education, teacher performance